Handbook of Mathematical Formulas - Bartsch, Hans Jochen (New York: Academic Press, 1974)
The purpose of this compilation of formulas is to provide the necessary educational aid. The book starts from secondary school mathematics and is primarily intended for students of technical schools, colleges and universities. Additionally, the scope of this collection of formulas covers the whole field from the fundamental rules of arithmetic, via analytic geometry and infinitesimal calculus through to FOURIER's series and the fundamentals of probability calculus. Subjects of topical interest such as matrices, statistics, linear optimization, Boolean algebra, and LAPLACE's transforms are also included.
Translation of the 9th ed. of Mathematische Formeln.
Includes index.
ne 7/03/2018
Loan
Keywords: Mathematics